Reviews of national science policy. Netherlands. - Organisation for Economic Co-operation and Development (Paris : Organisation for Economic Co-operation and Development, 1973)
This report is the sixteenth in the series of Reviews of National Science Policy by the Organisation for Economic Co-operation and Development. It has two purposes: first, to enable the countries concerned to appraise the political, economic, and structural aspects of the action taken to reinforce the role of scientific and technical research in the achievement of national goals; and second, to enrich the pool of available knowledge on the content of science policies and their role as an instrument of government. In the first part of this document a background report is provided, with information organized under the headings: The Scale and Dynamics of R & D Activity, Institutions of Science Policy, Prosperity Through Research, Research in the Service of the Community, University in Search of New Ends, and Science Policy and National Goals. In the second part, research and development activity is analyzed in the three main branches--industry, government, and universities--and points are raised which should be considered for its future development. (DT)
Availability: OECD Publications Center, Suite 1207, 1750 Pennsylvania Avenue, N.W., Washington, D. C. 20006 ($8.75).
Microfiche.
Keywords: Science and state -- Netherlands